Tension between the need for certainty and numerous uncertainties: a focus group study on various perspectives on a potential genomic newborn screening program in Germany - Doll, Elena Sophia; Mahal, Julia; Alex, Karla; Lerch, Seraina Petra; Kölker, Stefan; Schaaf, Christian P.; Winkler, Eva C.; Ditzen, Beate (Journal of genetic counseling, 2025)
The advancement of genome sequencing technology and its potential application in newborn screening is being discussed in various countries. Genomic newborn screening (gNBS) can provide parents with information about their child's genetic susceptibility for known disorders. However, it also presents ethical and psychosocial challenges. This study was carried out with a view toward the possible introduction of gNBS in Germany. Due to the existing challenges, it is crucial to understand different perspectives of relevant groups in Germany before implementing gNBS. Four online focus groups were conducted with parents, patient representatives, and healthcare professionals to explore perceived opportunities and challenges, as well as needs regarding a potential gNBS program. Discussions with altogether 24 participants were semi-structured using a pre-defined interview guide. Sessions were audio-visually recorded and transcripts were analyzed using a structuring qualitative content analysis combining both deductive and inductive methods. Participants expressed positive views about gNBS but also reservations about a gNBS program and posed requirements for operating conditions. One salient theme that emerged was hope for certainty through gNBS in the face of numerous uncertainties. The study complements the perspective of patient representatives, providing further insight into the subject matter. This is a valuable contribution as they possess a comprehensive understanding of the medical, psychological, and ethical considerations involved. Patient representatives placed particular emphasis on the advantages of avoiding a diagnostic odyssey and the significance of support systems. The results provide first insights into different views on gNBS in Germany. These views can inform the potential preparation of a gNBS program in Germany, particularly with regard to information and consent requirements. Implications for practice, such as informing and educating parents about gNBS during pregnancy, can be derived from the study.
Online veröffentlicht: 16. Mai 2025
Gesehen am 29.09.2025